Investment consultants and green investment: risking stranded advice? - Caldecott, B; Rook, D (Smith School of Enterprise and the Environment, 2015)
Investment consultants are key ‘gatekeepers’ for asset owners, such as pension funds, and are instrumental in determining whether products and services are accepted or not by the financial community. Empirical research conducted as part of this study suggests that inadequate investment consultant-asset owner relationships are hindering the development of green investment. This study investigates this problem and examines its potential causes. We make recommendations to remedy these issues, set out new criteria to assess the capabilities of investment consultants with respect to green investment, and outline a new algorithmic tool to empower asset owners.